Sanksi Rehabilitasi Bagi Prajurit TNI yang Menjadi Terpidana Penyalahgunaan Narkotika (Studi Kasus di Pengadilan Militer II – 08 Jakarta) - Muhamad Nur Ardhy; Muhyi Mohas; Reine Rofiana (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2021)
A TNI soldier is required to have good mentality, discipline, and good morals and ethics. The application of law against TNI soldiers is not only in the form of the application of military criminal law, but also criminal law outside the military criminal law, one of which is the crime of narcotics abuse. The sentencing of TNI soldiers who are convicted of narcotics abusers still refers to Law no. 35 of 2009. Almost all decisions made by military judges, especially those of military judges at the Military Court II – 08, Jakarta, related to narcotics abuse resulted in imprisonment and dismissal from military service without any rehabilitation efforts. This is of course very contrary to the legal objectives of Law no. 35 of 2009 concerning Narcotics. The method used in this study uses a normative juridical method with a statutory approach. This study found problems in imposing sanctions on military members who become narcotics abusers, where the Narcotics Law states that there are rehabilitation sanctions in addition to prison sanctions but in practice the sanctions given to military members who become narcotics abusers are only limited to prison sanctions and dismissal from military service without given a rehabilitation sanction. This shows that sanctions against narcotics abuse by members of the TNI in the Military Court II – 08, Jakarta are still in the form of retributive sanctions, namely imprisonment and dismissal from military service, as well as enforcement of rehabilitation law for TNI members who are convicted of drug abuse still not done.